Anti-Phosphatidylserine-Prothrombin Antibodies are Associated with Outcome in a TIA Cohort - Mullen, Michael T.; Messé, Steven R.; Kasner, Scott E.; Sansing, Lauren; Husain, M R.; Norman, Gary L.; Shums, Zakera; Cucchiara, Brett L. (Frontiers in Neurology, 2012)
Background: Antiphospholipid antibodies (aPLs) have been associated with thrombosis in the antiphospholipid antibody syndrome (APS) and with atherosclerotic vascular events in patients without APS. We examined the significance of aPLs in transient ischemic attack (TIA). Patients/Methods: Patients with TIA <48 hours from symptom onset were prospectively enrolled. Traditional aPLs, including anti-cardiolipin (aCL) and β2-glycoprotein-I (β2GPI), and newer aPLs, including anti-phosphatidylserine/prothrombin (aPS/PT), β2GPI Domain 4/5 and β2GPI Domain 1 were measured. Primary outcome was a composite of stroke or death within 90 days or identification of a high-risk stroke mechanism. Secondary outcomes were stroke or death and the presence of clinical/sub-clinical atherosclerosis. Results: Over 4.5 years, 167 patients were enrolled. 41 patients (25%) had the composite endpoint. Antibodies were measured in 158 subjects. aPS/PT IgG antibodies were significantly associated with stroke/death (OR 16.3 95% CI 2.3-116.7 p=0.005) and were non-significantly associated with the composite endpoint (OR 4.7 95% CI 0.8-29.2 p=0.10). In multivariate analysis adjusting for ABCD2 risk score, aPS/PT IgG remained associated with stroke/death (OR 15.7 95% CI 2.0-125.6 p=0.009). Other aPLs were not associated with clinical outcome and no association between APLs and atherosclerosis was identifed. Conclusion: In contrast to other aPLs, anti-phosphatidylserine/prothrombin IgG antibodies are independently associated with stroke or death in patients with TIA.